Electrical transport properties of an organic semiconductor on polyaniline doped by boric acid - Yakuphanoğlu, Fahrettin; Senkal, B. Filiz (Wiley, 2008)
The electrical conductivity, thermoelectric power, and dielectric properties of polyaniline doped by boric acid (PANI-B) have been investigated. The room temperature electrical conductivity of PANI-B was found to be 1.02 x 10(-4) S cm(-1). The thermoelectric power factor for the polymer was found to be 0.64 mu W m(-1) K-2. The optical band gap of the PANI-B was determined by optical absorption method, and the PANI-B has a direct optical band gap of 3.71 eV. The alternating charge transport mechanism of the polymer is based on the correlated barrier hopping (CBH) model. The imaginary part of the dielectric modulus for the PANI-B suggests a temperature dependent dielectric relaxation mechanism. Electrical conductivity and thermoelectric power results indicate that the PANI-B is an organic semiconductor with thermally activated conduction mechanism. Copyright (C) 2008 John Wiley & Sons, Ltd.
Keywords: organic semiconductor; polyaniline; electrical properties